(untitled) - Escott, John (Oxford, 1998)
Agatha Christie's murder mysteries are famous all over the world. She wrote more than seventy books and they have sold millions of copies. This is a story about Agatha Christie's life. What kind of person was she? How much do we know about her? She was rich, famous, and twice married. And there was a mystery in her life, too...
Keywords: English fiction,English literature; 20th century